PVC (polyvinyl chloride) foaming material as well as preparation method and application thereof
By adjusting the dosage of chores, organic tin, and puppet nitrogen diced pupa in PVC foaming materials, the problem of poor mechanical properties of PVC foaming materials is solved, preparing low density, high tensile strength, broken and elongated elongation Excellent PVC foam material with high rate.
Patent Information
- Application Number
- CN202411635475.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-28
AI Technical Summary
The mechanical properties of existing PVC foaming materials are poor and difficult to meet certain application needs.
By adjusting the dosage of Tancho rubber (NBR), organic tin, and puppet nitrogen diced, prepare an excellent PVC foam material. The preparation of this material includes a polyvinyl chloride resin, a modified agent, a foaming agent, and a stabilizer. The modifier is chore rubber, the foaming agent is puppet nitrogen diced, and the stabilizer is organic tin.
The mechanical performance of the PVC foaming material is improved, the density is 0.853g/cm3, the stretching strength reaches 5.455MPa, and the breakdown rate of the break is 184.6 %.
Smart Images

Figure CN119371761A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of plastic preparation, and in particular relates to a PVC foam material and a preparation method and application thereof. Background Art
[0002] Foam is a type of plastic, also known as porous plastic. It is a type of composite polymer material with a large number of interconnected or unconnected gas micropores dispersed in solid plastics, which significantly reduces the apparent density. Due to its special structure, it has special properties. Foam plastics have the comprehensive characteristics of foam porosity and matrix resin properties, which makes this type of plastic light in weight, high in specific strength, able to absorb impact loads, and good in thermal insulation. Compared with ordinary plastics, due to the presence of a large number of gas micropores, low-density foam can save raw materials to produce lighter products, and can achieve the purpose of lightweighting materials without losing the performance of the materials. The products are cost-effective and are widely used in industry, agriculture, construction, daily necessities and their packaging and transportation.
[0003] PVC foam material is a kind of foam plastic. Compared with other foam materials, foamed PVC material has excellent mechanical properties, adhesion, processability, low cost and other advantages. It has obvious advantages as a sole material; however, due to the poor mechanical properties of PVC resin, the current PVC foam material still has the above disadvantages. Summary of the invention
[0004] The present invention develops a PVC foam material, and can prepare a PVC foam material with excellent mechanical properties by setting different amounts of nitrile rubber (NBR), organic tin and azobisisobutyronitrile.
[0005] In order to achieve the above object, the present invention can adopt the following technical solutions:
[0006] The present invention provides a PVC foam material on one hand. The raw materials for preparing the PVC foam material include: polyvinyl chloride resin, a modifier, a foaming agent and a stabilizer. The modifier is nitrile rubber.
[0007] Preferably, the above-mentioned preparation raw materials meet one or more combinations of the following conditions: (a) the modifier is nitrile rubber; (b) the foaming agent is azobisisobutyronitrile; (c) the stabilizer is organic tin; (d) the mass ratio of the modifier to the polyvinyl chloride resin is (20-50):100; (e) the mass ratio of the foaming agent to the polyvinyl chloride resin is (2-8):100; (f) the mass ratio of the stabilizer to the polyvinyl chloride resin is (0.8-2):100.
[0008] (a) the blowing agent is one or more combinations of azobisisobutyronitrile and citric acid;
[0009] (b) the stabilizer is one or more combinations of organic tin, lead stearate, barium stearate or rare earth stabilizers;
[0010] (c) the mass ratio of the modifier to the polyvinyl chloride resin is (20-50):100;
[0011] (d) the mass ratio of the foaming agent to the polyvinyl chloride resin is (2-8):100;
[0012] (e) The mass ratio of the stabilizer to the polyvinyl chloride resin is (0.8-2):100.
[0013] More preferably, the above-mentioned raw materials meet one or more combinations of the following conditions: (a) the mass ratio of the modifier to the polyvinyl chloride resin is 40:100; (b) the mass ratio of the foaming agent to the polyvinyl chloride resin is 4:100; (c) the mass ratio of the stabilizer to the polyvinyl chloride resin is 1.2:100.
[0014] Preferably, the above-mentioned raw materials for preparation further include a plasticizer, a cell nucleating agent, a cell regulator and an inorganic filler.
[0015] Preferably, the above-mentioned preparation raw materials meet one or more combinations of the following conditions: (a) the plasticizer is dioctyl phthalate; (b) the cell nucleating agent is titanium dioxide; (c) the cell regulator is ACR-401; (d) the inorganic filler is calcium carbonate; (e) the mass ratio of the plasticizer to the polyvinyl chloride resin is (55-65):100; (f) the mass ratio of the cell nucleating agent to the polyvinyl chloride resin is (1-3):1000; (g) the mass ratio of the cell regulator to the polyvinyl chloride resin is (11-13):100; (h) the mass ratio of the inorganic filler to the polyvinyl chloride resin is (0.5-1.5):100.
[0016] More preferably, the above-mentioned preparation raw materials meet one or more combinations of the following conditions: (a) the mass ratio of plasticizer to polyvinyl chloride resin is 60:100; (b) the mass ratio of cell nucleating agent to polyvinyl chloride resin is 2:100; (c) the mass ratio of cell regulator to polyvinyl chloride resin is 12:100; (d) the mass ratio of inorganic filler to polyvinyl chloride resin is 1:100.
[0017] Another aspect of the present invention provides a method for preparing the PVC foam material of the present invention, which comprises: mixing, kneading and foaming the raw materials to obtain the PVC foam material.
[0018] Preferably, the above preparation method satisfies one or more combinations of the following conditions:
[0019] (a) firstly mix polyvinyl chloride resin, stabilizer, plasticizer, cell nucleating agent, cell regulator and inorganic filler to obtain a first mixture; pre-plasticize the first mixture and stir it to obtain a second mixture; wherein the pre-plasticization and stirring are repeated more than once; the second mixture is mixed with a modifier and a foaming agent and then kneaded to obtain a PVC foam material; (b) the kneading temperature is 100°C-120°C; (c) the foaming is performed by using a mold and the hot pressing temperature is 160°C-180°C; (d) the foaming is performed by using a mold and the hot pressing time is 8min-10min; (e) the foaming is performed by using a mold and the cold pressing time is 4min-7min.
[0020] Another aspect of the present invention provides a shoe sole, which is made of the PVC foam material of the present invention.
[0021] Another aspect of the present invention provides a shoe comprising the sole of the present invention.
[0022] The beneficial effects of the present invention include at least: the present invention can prepare a PVC foam material with excellent mechanical properties by changing the dosage of the modifier, stabilizer and foaming agent, and the density can be 0.853g / cm 3 , the tensile strength can reach 5.455MPa, and the elongation at break can reach 184.6%. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the appearance of PVC after mixing;
[0024] Figure 2 This is the appearance of the PVC board after molded foaming;
[0025] Figure 3 The effect of NBR dosage on the density of PVC foam material;
[0026] Figure 4 The effect of NBR dosage on the tensile strength and elongation at break of PVC foam materials;
[0027] Figure 5 The appearance of the PVC foam materials prepared in Example 3 and Example 7;
[0028] Figure 6 The effect of organic tin dosage on the density of PVC foam material;
[0029] Figure 7 The effect of the amount of organic tin on the tensile strength and elongation at break of PVC foam material;
[0030] Figure 8 This is a cell distribution diagram of the foamed material prepared in Example 8;
[0031] Fig. 9 This is a cell distribution diagram of the PVC foam material prepared in Example 3;
[0032] Fig.10 This is a cell distribution diagram of the PVC foam material prepared in Example 9;
[0033] Fig.11 The effect of AIBN dosage on the density of PVC foam material;
[0034] Fig.12 This is the effect of AIBN dosage on the elongation at break and tensile strength of PVC foam materials. DETAILED DESCRIPTION
[0035] The examples are provided to better illustrate the present invention, but the present invention is not limited to the examples. Therefore, those skilled in the art may make non-essential improvements and adjustments to the implementation scheme according to the above invention content, which still fall within the protection scope of the present invention.
[0036] The terms used herein are only used to describe specific embodiments and are not intended to limit the present disclosure. Unless the context has a significantly different meaning, expressions in the singular include expressions in the plural. As used herein, it should be understood that terms such as "include", "have", "include" are intended to indicate the presence of features, numbers, operations, components, parts, elements, materials or combinations. The terms of the present invention are disclosed in the specification, and are not intended to exclude the possibility that one or more other features, numbers, operations, components, parts, elements, materials or combinations thereof may exist or may be added. As used herein, " / " may be interpreted as "and" or "or", depending on the circumstances.
[0037] The embodiment of the present invention provides a PVC foam material, the raw materials for preparing the PVC foam material include: polyvinyl chloride resin, a modifier, a foaming agent and a stabilizer, and the modifier is nitrile rubber (NBR).
[0038] It should be noted that the role of the modifier is to reduce the density of the foamed PVC material and increase the elongation at break; in the present invention, the modifier is selected from nitrile rubber (NBR); NBR has good oil resistance, heat resistance and weather resistance; and NBR and PVC have good compatibility, which makes it possible to add NBR to the PVC foaming system for blending and modification. In the NBR / PVC blended foaming system, after adding an appropriate amount of NBR, the elasticity, oil resistance and weather resistance of the foamed polyvinyl chloride material can be improved, and after modification, a relatively small density and good mechanical properties must still be maintained.
[0039] In some specific examples, the above-mentioned raw materials meet one or more combinations of the following conditions:
[0040] (a) The foaming agent is one or more of azobisisobutyronitrile and citric acid; specifically, the foaming agent functions to generate bubbles, and the foaming agent may be a foaming agent known in the art; in the present invention, azobisisobutyronitrile is preferred, which decomposes to generate nitrogen, forms pores and expands the pores, and the decomposition temperature of AIBN generates less heat, and the uniformity of the generated pores is better; and the gas emission of AIBN is lower than that of the AC foaming agent, and its decomposition temperature is also lower, and the heat generated during decomposition is also less, which makes the process of preparing low-density foamed products with AIBN more stable, especially when preparing large-volume foamed products, the large amount of heat accumulated inside will not affect the uniformity of the pores and cause the decomposition of PVC; temperature is the most important factor affecting the decomposition rate of AIBN, and the pressure has little effect on the decomposition of AIBN, and it is also insensitive to other additives;
[0041] (b) The stabilizer is one or more combinations of organic tin, lead stearate, barium stearate or rare earth stabilizers; specifically, the purpose of the stabilizer is to improve its stability to light and heat, and the stabilizer is achieved by replacing unstable Cl atoms and destroying the double bond conjugated system, otherwise the color of the product is easily deepened and the mechanical properties are reduced; common stabilizers include organic tin stabilizers, lead salt stabilizers and rare earth stabilizers; compared with the other two stabilizers, organic tin stabilizers have better color retention than lead salt stabilizers, are non-toxic, more environmentally friendly, and have a more mature process than rare earth stabilizers; therefore, organic tin is preferably used as a stabilizer in the present invention;
[0042] (c) the mass ratio of the modifier to the polyvinyl chloride resin is (20-50):100; specifically, the mass ratio of the modifier to the polyvinyl chloride resin affects the mechanical properties of the prepared PVC foam material. In the present invention, the mass ratio can be (20-50):100, such as 25:100, 30:100, 35:100, 40:100 or 45:100; preferably 40:100. When the mass ratio is 40:100, the comprehensive performance is better in terms of comprehensive density, tensile strength and elongation at break;
[0043] (d) the mass ratio of the foaming agent to the polyvinyl chloride resin is (2-8):100; specifically, the mass ratio of the foaming agent to the polyvinyl chloride resin affects the mechanical properties of the prepared PVC foam material, and in the present invention, (2-8):100, 3:100, 5:100 or 7:100 can be selected; in the present invention, 4:100 is preferred, and under this ratio, the comprehensive performance of density, tensile strength and elongation at break is better;
[0044] (e) The mass ratio of the stabilizer to the polyvinyl chloride resin is (0.8-2):100; specifically, the mass ratio of the stabilizer to the polyvinyl chloride resin affects the mechanical properties of the prepared PVC foam material. The present invention can select (0.8-2):100, such as 1:100, 1.3:100, 1.5:100 or 1.8:100; more preferably 1.2:100, under which the comprehensive performance of density, tensile strength and elongation at break is better.
[0045] In some specific examples, the above-mentioned preparation raw materials further include a plasticizer, a cell nucleating agent, a cell regulator and an inorganic filler.
[0046] It should be noted that, in order to further improve the mechanical properties of the PVC foam material of the present invention, a plasticizer, a cell nucleating agent, a cell regulator and an inorganic filler may be further added to the raw materials for preparation.
[0047] In some specific examples, the above-mentioned raw materials meet one or more combinations of the following conditions:
[0048] (a) The plasticizer is dioctyl phthalate; the plasticizer is dioctyl phthalate (DOP); specifically, the function of the plasticizer is to improve the foaming performance and increase the softness and plasticity of the foam material; in the present invention, all plasticizers known in the art can be selected, preferably dioctyl phthalate, DOP enters between the molecules of PVC, increases the distance between the molecules, weakens the intermolecular force, increases the viscosity of the foaming reaction system, and increases the plasticity of PVC;
[0049] (b) the cell nucleating agent is titanium dioxide; specifically, the cell nucleating agent is used to promote the formation of cell nuclei during the foaming process of PVC; in the present invention, cell nucleating agents known in the art can be selected, and titanium dioxide is preferred in the present invention; titanium dioxide can not only promote the formation of cell nuclei during the foaming process of PVC, but also be used as a pigment to make the color of the foamed PVC sheet brighter and whiter;
[0050] (c) the cell regulator is ACR-401; the cell regulator is ACR-401; specifically, the cell regulator is used to plasticize and melt PVC, so that the strength and ductility of the melt in the foaming process are higher and the formation of cells is more stable; ACR-401 is preferred in the present invention, and its performance is better than other cell regulators;
[0051] (d) the inorganic filler is calcium carbonate; specifically, in the present invention, the inorganic filler is added to the system, the important function of which is to increase the strength of the foamed material and improve the toughness of the foamed material; the inorganic filler can be any inorganic filler known in the art, such as calcium carbonate, etc., more preferably nano calcium carbonate, which has a better effect than general calcium carbonate;
[0052] (e) the mass ratio of the plasticizer to the polyvinyl chloride resin is (55-65):100; specifically, the mass ratio of the plasticizer to the polyvinyl chloride resin affects the mechanical properties of the prepared PVC foam material. The present invention can select (55-65):100, such as 58:100, 60:100 or 63:100; more preferably 60:100, under which the comprehensive performance of density, tensile strength and elongation at break is better;
[0053] (f) the mass ratio of the cell nucleating agent to the polyvinyl chloride resin is (1-3):1000; specifically, the mass ratio of the cell nucleating agent to the polyvinyl chloride resin is 2:100; specifically, the mass ratio of the cell nucleating agent to the polyvinyl chloride resin affects the mechanical properties of the prepared PVC foam material. The present invention can select (1-3):100, such as 1.5:100, 2:100 or 2.5:100, preferably 2:100. Under this ratio, the comprehensive performance of density, tensile strength and elongation at break is better;
[0054] (g) the mass ratio of the cell regulator to the polyvinyl chloride resin is (11-13):100; specifically, the mass ratio of the cell regulator to the polyvinyl chloride resin affects the mechanical properties of the prepared PVC foam material. In the present invention, 11-13:100 can be selected, such as 11.5:100, 12:100 or 12.5:100; more preferably 12:100, under which the comprehensive performance of density, tensile strength and elongation at break is better;
[0055] (h) The mass ratio of the inorganic filler to the polyvinyl chloride resin is (0.5-1.5):100; specifically, the mass ratio of the inorganic filler to the polyvinyl chloride resin affects the mechanical properties of the prepared PVC foam material. In the present invention, the mass ratio of (0.5-1.5):100 can be selected, such as 0.8:1, 1:100 or 1.2:100; preferably 1:100; under this ratio, the comprehensive performance of density, tensile strength and elongation at break is better.
[0056] It should be noted that, among the above conditions (a) to (h), the raw materials for preparation of the present invention may satisfy one of the conditions, preferably satisfy two or more of the conditions; more preferably satisfy all of the above conditions at the same time.
[0057] The embodiment of the present invention further provides a method for preparing the PVC foam material of the present invention, which comprises: mixing, kneading and foaming the raw materials to obtain the PVC foam material.
[0058] It should be noted that the mixing, kneading and foaming in the above preparation method are all well-known operation methods in the art, and are applicable to all mixing, kneading and foaming methods in the art.
[0059] In some specific examples, the above preparation method satisfies one or more combinations of the following conditions:
[0060] (a2) firstly mixing polyvinyl chloride resin, stabilizer, plasticizer, cell nucleating agent, cell regulator and inorganic filler to obtain a first mixture; pre-plasticizing the first mixture and stirring it to obtain a second mixture; wherein the pre-plasticizing and stirring are repeated more than once; mixing the second mixture with a modifier and a foaming agent and then kneading them to obtain a PVC foam material; specifically, in order to allow the stabilizer to be more fully absorbed by the polyvinyl chloride resin, the raw materials for preparation can be added step by step, for example, the polyvinyl chloride resin, stabilizer, plasticizer, cell nucleating agent, cell regulator and calcium carbonate can be mixed first, and then heated for pre-plasticization, and then stirred after pre-plasticization, and the mixture can be taken out and stirred once after heating for 4min-5min, and the mixture can be stirred more than twice, for example, 4-5 times; then the pre-plasticized and stirred mixture is mixed with a modifier and a foaming agent and then kneaded to obtain a PVC foam material;
[0061] (b2) the mixing temperature is 100°C to 120°C; for example, 105°C, 110°C or 115°C;
[0062] (c2) Foaming is performed using a mold, and the hot pressing temperature is 160°C-180°C; for example, 165°C, 170°C or 175°C;
[0063] (d2) Foaming is performed using a mold, and the hot pressing time is 8min-10min; 8.5min, 9min or 9.5min, etc.;
[0064] (e2) Foaming is done by using a mold, and the cold pressing time is 4 minutes to 7 minutes; for example, 5 minutes, 6 minutes or 6.5 minutes.
[0065] It should be noted that the commonly used polymer foaming molding processes mainly include three categories: compression molding, extrusion molding and injection molding; among them, injection molding can form foam plastic products with complex shapes and fine patterns on the surface at one time, and the product has good repeatability and high quality, but has high requirements on equipment; extrusion molding has high molding efficiency, but has the disadvantages of low surface strength and poor finish; compression molding is relatively simple and easy to operate, so compression molding (i.e., mold foaming) is selected in the present invention; in addition, compression molding can be divided into two types, one-step compression molding and two-step compression molding. In the present invention, one-step compression molding can be preferred, that is, the uniformly mixed materials are placed in a mold and foamed and shaped by high temperature and high pressure, and the foamed PVC material is obtained by one-time molding.
[0066] It should also be noted that among the above conditions (a2) to (e2), any one of the conditions can be satisfied, preferably two or more conditions are satisfied at the same time; more preferably all of the above conditions are satisfied at the same time; and even more preferably, the preferred condition of satisfying all of the above conditions is satisfied at the same time.
[0067] It should also be noted that the raw materials prepared in the present invention may satisfy any one of conditions (a) to (h) and (a2) to (e2), preferably satisfying two or more conditions at the same time; more preferably satisfying all of the above conditions at the same time; and even more preferably, satisfying the preferred conditions of all of the above conditions at the same time.
[0068] An embodiment of the present invention provides a shoe sole, which is made of the PVC foam material of the present invention.
[0069] It should be noted that the PVC foam material of the present invention can be prepared into a shoe sole. Based on the excellent mechanical properties of the PVC foam material, the prepared shoe sole also has excellent mechanical properties.
[0070] An embodiment of the present invention provides a shoe comprising the sole of the present invention.
[0071] It should be noted that the soles made of the PVC foam material in the present invention can be made into shoes, and other structures of the shoes are well known in the art.
[0072] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific examples, but the content of the present invention is not limited to the following examples.
[0073] 1. Sample preparation
[0074] Example 1 to Example 4
[0075] (1) Weigh the required chemicals according to the formula ratio, put the weighed polyvinyl chloride resin (PVC), stabilizer (organic tin), plasticizer (DOP), cell nucleating agent (titanium dioxide), cell regulator (ACR-401) and calcium carbonate into a pre-prepared beaker and stir, then put it into an oven at 100-110°C for pre-plasticization, and take it out of the oven and stir it every 5 minutes, for a total of 5 times, in order to allow DOP to be completely absorbed by PVC;
[0076] (2) The temperature of the third zone of the mixing platform is set to 110° C., stirring is turned on, and the mixed and stirred mixture is poured into an internal mixer for mixing. After the mixture is melted, a modifier powder nitrile rubber (NBR) is added, and then a foaming agent azobisisobutyronitrile (AIBN) is added. After the internal pressure of the mixing container is stable for 1 minute, the mixed PVC is taken out for standby use;
[0077] (3) Molding foaming: first turn on the hot press switch, set the parameters, and adjust the temperature of the vulcanizer to 170℃. After the parameters are set, select the mold. The mold should be a small mold with a length*width of 160mm*160mm and a thickness of 4mm. Before putting the rolled PVC sheet into the mold, a layer of polyester film needs to be laid to protect the mold. Then, the molding foaming can be carried out. After hot pressing for 9 minutes, it is immediately transferred to the hot press for cold pressing for 6 minutes. Then, the foamed PVC board is taken out of the mold and left to stand at room temperature for 24 hours, and then a standard sample is prepared to test the performance.
[0078] The formulation ratios of Examples 1 to 4 are shown in Table 1 below, and the other steps are carried out according to the steps in the above preparation method.
[0079] Table 1 Foam formulations of Examples 1 to 4
[0080] Example PVC DOP Organic tin <![CDATA[TiO2]]> AIBN ACR-401 NBR Nano Calcium Carbonate Example 1 100 60 1.2 2 4 12 20 1 Example 2 100 60 1.2 2 4 12 30 1 Example 3 100 60 1.2 2 4 12 40 1 Example 4 100 60 1.2 2 4 12 50 1
[0081] In addition, in Example 3, the PVC after mixing in step (2) is as follows Figure 1 As shown, the PVC board after molded foaming in step (3) is as follows Figure 2 shown.
[0082] Example 5 to Example 7
[0083] Examples 5 to 7 are the same as Example 3. The difference between Examples 5 to 7 and Example 3 is that the amount of organic tin added is different. The formula ratios of Examples 5 to 7 and Example 3 are shown in Table 2 below.
[0084] Table 2 Foam formula of Example 3, Example 5 to Example 7
[0085] Example PVC DOP Organic tin <![CDATA[TiO2]]> AIBN ACR-401 NBR Nano Calcium Carbonate Example 5 100 60 0.8 2 4 12 40 1 Example 3 100 60 1.2 2 4 12 40 1 Example 6 100 60 1.6 2 4 12 40 1 Example 7 100 60 2.0 2 4 12 40 1
[0086] Example 8 to Example 10
[0087] Embodiments 8 to 10 are the same as Embodiment 3. The difference between Embodiments 8 to 10 and Embodiment 3 is that the amount of organic tin added is different. The formula ratios of Embodiments 8 to 10 and Embodiment 3 are shown in Table 3 below.
[0088] Table 3 Foam formulations of Example 3, Example 8 to Example 10
[0089] Example PVC DOP Organic tin <![CDATA[TiO2]]> AIBN ACR-401 NBR Nano Calcium Carbonate Example 8 100 60 1.2 2 2 12 40 1 Example 3 100 60 1.2 2 4 12 40 1 Example 9 100 60 1.2 2 6 12 40 1 Example 10 100 60 1.2 2 8 12 40 1
[0090] Comparative Example 1
[0091] The difference between Comparative Example 1 and Example 3 is that the modifier is different. The modifier used in Comparative Example 1 is calcium oxide, and the rest is the same as Example 3.
[0092] Comparative Example 2
[0093] The difference between Comparative Example 1 and Example 3 is that the blowing agent is different. The blowing agent used in Comparative Example 1 is azodicarbonamide (AC), and the rest is the same as Example 3.
[0094] 2. Sample testing
[0095] In the following tests, tensile strength and elongation at break are used as indicators for mechanical property testing. The instrument required for the test is an electronic universal testing machine (UTM5105X). The test is carried out in accordance with GB / T6344-2008. Before the test, the PVC board needs to be prepared by standard sample preparation. The length, width and thickness of the sample strip are 160mm×10mm×4mm. The universal testing machine is controlled by a computer to move the fixture at a tensile rate of 200mm / min. The stress-strain curve of the foamed PVC material during stretching can be measured to obtain the maximum load F. Among them, the tensile strength formula is: T S =F / A×10 3 , T S Tensile strength, unit (kPa); F Maximum load, unit Newton (N); A Average original cross-sectional area of the specimen, unit square millimeter (mm 2 ); Elongation at break: E b =(L-L0) / L0×100%,E b Elongation at break, expressed in %; L specimen breaking gauge length, in millimeters (mm); L0 specimen original gauge length, in millimeters (mm).
[0096] In the following tests, the density test is carried out in accordance with GB / T6343-2009, and the test formula is ρ = M / V × 10 6 , unit: kg / m 3 ρ apparent density, unit: kilograms per cubic meter (kg / m 3 ); M is the mass of the sample, in grams (g); V is the volume of the sample, in cubic millimeters (mm 3 ); In addition, the water displacement method is used to calculate the volume. First, the spline is made into a rectangular spline. Then, the spline is placed in a beaker filled with one-third water. Because the density of the spline is smaller than that of water, a small wire is needed to tie the spline. Then, the volume of the spline is calculated based on the rising water level in the beaker. However, the volume measured by this method will be smaller because the spline has pores and water will enter, resulting in a higher density.
[0097] (I) Tests of Examples 1 to 4
[0098] The density, tensile strength and elongation at break of the foamed materials prepared in Examples 1 to 4 were tested according to the above method. The results are shown in Table 4 and Figure 3 and Figure 4 shown.
[0099] Table 4 Performance test results of the foaming materials prepared in Examples 1 to 4
[0100] Example <![CDATA[Density / g*cm 3 > Tensile strength / MPa Elongation at break / % Example 1 0.987 5.555 179.6 Example 2 0.834 4.608 189.6 Example 3 0.853 5.455 184.6 Example 4 0.838 5.08 212.9
[0101] From Table 4 and Figure 3 It can be seen that as the amount of NBR increases, the density decreases significantly at first, and then increases slightly. When the amount of NBR is 40, the density is the lowest value of 0.853g / cm 3 Then, the density increases slightly with the increase of NBR dosage. When the NBR dosage exceeds 40%, the viscosity of the NBR / PVC foaming system increases. The formation of bubbles is hindered, so the density shows a slightly increasing trend.
[0102] From Table 4 and Figure 4 It can be seen that the tensile strength is the highest when the NBR dosage is 20 parts, and the NBR dosage is 20, 40 and 50 parts respectively, and the overall trend is downward, but the overall change is not large. The tensile strength is the lowest when the NBR dosage is 30 parts. As the NBR dosage increases, the elongation at break shows an overall upward trend, and there is a more obvious improvement when it increases to 50 parts. The change in the NBR dosage between 20 and 40 parts is small.
[0103] Considering the density, tensile strength and elongation at break, the comprehensive performance is best when the NBR dosage is 40 parts.
[0104] (II) Embodiment 3 and Embodiments 5 to 7
[0105] The appearance of the PVC foam materials prepared in Example 3 and Example 7 was observed. Figure 5 As shown, the results show that the amount of organotin has a great influence on the color of the PVC foam material. The increase of organotin (Example 7) can make the color of the PVC foam material whiter and brighter.
[0106] In addition, the density, tensile strength and elongation at break of the foamed materials prepared in Example 3 and Example 5 to Example 7 were tested according to the above method. The results are shown in Table 5 and Figure 6 and Figure 7 shown.
[0107] Table 5 Performance test results of the foaming materials prepared in Example 3 and Example 5 to Example 7
[0108] Example <![CDATA[Density / g*cm 3 > Tensile strength / MPa Elongation at break / % Example 5 0.784 4.956 159.5 Example 3 0.853 5.455 184.6 Example 6 0.889 5.177 197.8 Example 7 0.897 5.288 164.5
[0109] From Table 5 and Figure 6It can be seen that the density curve shows an overall upward trend, that is, as the amount of organotin increases, the density of foamed PVC also increases.
[0110] From Table 5 and Figure 7 It can be seen that the elongation at break first increases and then decreases, reaching the maximum value when the amount of organotin is 1.6 parts, while the tensile strength first increases, then decreases, and then increases again, and the tensile strength reaches the maximum value when the amount of organotin is 1.2 parts. Although the density is the smallest when the amount of organotin is 0.8 parts, the elongation at break and the tensile strength are both small at this time. When the amount of organotin is 1.2, the density increases, but the values of the elongation at break and the tensile strength are both high.
[0111] Taking the above into consideration, the comprehensive density, tensile strength and elongation at break, the best dosage of organic tin is 1.2 parts.
[0112] (III) Embodiment 3 and Embodiment 8 to Embodiment 10
[0113] The cell distribution of the foamed materials prepared in Example 3, Example 8 and Example 9 was observed using an optical microscope (OPTEC, Chongqing Aote Optical Instrument Co., Ltd.). Figure 8 , Fig. 9 and Fig.10 As shown in the figure, the number of pores is small and the position distribution is relatively scattered. It can be concluded that the density of the pores is low, and the PVC foamed board with low foaming rate is obtained. The foaming effect is not very ideal, indicating that this formula system needs further optimization, both in terms of formula components and molding process. Analyzing the reasons for the nucleation mechanism, the small number of pores may be due to the small number of nucleation points or the small amount of supersaturated gas. In terms of nucleation points, the role of calcium carbonate in the selection of fillers is to increase the strength of the foamed PVC material, improve its toughness, and act as a nucleating agent together with titanium dioxide. If nano-scale calcium carbonate is used, it has better dispersibility and is a better choice. Supersaturated gas is mainly affected by the foaming agent. Compared with AC, AIBN has a smaller gas emission, which may be the main reason for the low foaming ratio. In addition, the decomposition temperature of AIBN is also lower than that of AC foaming agent. The selection of a high mixing temperature may cause AIBN to decompose prematurely during mixing, further reducing the foaming ratio.
[0114] in addition, Figure 8 In the middle, the pores are more regular and round in shape, but the number is less than that of the other two groups; Fig. 9 In the experiment, most of the pores are regular circles, some pores are combined, and the number of pores is large. Fig.10 In the embodiment, the number of cells is small, but the volume of cells is larger, which is presumably caused by more parallel cells. The irregular structure of the cells further verifies the conjecture of more parallel cells. Considering the shape, size and number distribution of the cells, the foaming effect of Example 3 is the best.
[0115] The density, tensile strength and elongation at break of the foamed materials prepared in Example 3 and Example 8 to Example 10 were tested according to the above method. The results are shown in Table 6 below. Fig.11 and Fig.12 shown.
[0116] Table 6 Performance test results of the foaming materials prepared in Example 3 and Example 8 to Example 10
[0117] Example <![CDATA[Density / g*cm 3 > Tensile strength / MPa Elongation at break / % Example 8 0.896 4.720 200.7 Example 3 0.853 5.455 184.6 Example 9 0.711 4.708 154.4 Example 10 0.645 4.179 163.5
[0118] From Table 6 and Fig.11 and Fig.12 It can be seen that with the increase of AIBN dosage, the density of PVC foam material decreases, the change trend of tensile strength is rising and then falling rapidly, and the tensile strength reaches the maximum value when the dosage of AIBN is 4 parts, and the change trend of elongation at break is first falling rapidly and then rising, and the elongation at break reaches the minimum value when the dosage is 6 parts. After comprehensive consideration of tensile strength, density, and elongation at break, the best dosage of AIBN is 4 parts.
[0119] (IV) Comparative Example 1 and Comparative Example 2 Test
[0120] The density, tensile strength and elongation at break of the foamed materials prepared in Example 3 and Comparative Examples 1 and 2 were tested according to the above method. The results are shown in Table 7 below.
[0121] Table 7 Performance test results of the foaming materials prepared in Example 3 and Comparative Examples 1 to 2
[0122] Example <![CDATA[Density / g*cm 3 > Tensile strength / MPa Elongation at break / % Example 3 0.853 5.455 184.6 Comparative Example 1 0.938 4.724 153.2 Comparative Example 2 0.903 4.368 158.4
[0123] It can be seen from Table 7 above that when calcium oxide is used as the modifier, the density of the prepared foamed material is significantly increased, and the tensile strength and elongation at break are significantly reduced; in addition, when azodicarbonamide (AC) is used as the foaming agent, the density is significantly increased, and the tensile strength and elongation at break are significantly reduced.
[0124] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be covered by the scope of the claims of the present invention.
Claims
1. A PVC foam material, characterized in that: The preparation raw materials include: polyvinyl chloride resin, modifier, foaming agent and stabilizer, and the modifier is nitrile rubber.
2. The PVC foam material according to claim 1, characterized in that: The raw materials for preparation meet one or more of the following conditions: (a) the blowing agent is one or more combinations of azobisisobutyronitrile and citric acid; (b) the stabilizer is one or more combinations of organic tin, lead stearate, barium stearate or rare earth stabilizers; (c) the mass ratio of the modifier to the polyvinyl chloride resin is (20-50):100; (d) the mass ratio of the foaming agent to the polyvinyl chloride resin is (2-8):100; (e) The mass ratio of the stabilizer to the polyvinyl chloride resin is (0.8-2):
100.
3. The PVC foam material according to claim 2, characterized in that: The raw materials for preparation meet one or more of the following conditions: (a) The mass ratio of the modifier to the polyvinyl chloride resin is 40:100; (b) The mass ratio of the foaming agent to the polyvinyl chloride resin is 4:100; (c) The mass ratio of the stabilizer to the polyvinyl chloride resin is 1.2:
100.
4. The PVC foam material according to any one of claims 1 to 3, characterized in that: The preparation raw materials also include plasticizer, cell nucleating agent, cell regulator and inorganic filler.
5. The PVC foam material according to claim 4, characterized in that: The raw materials for preparation meet one or more of the following conditions: (a) The plasticizer is dioctyl phthalate; (b) the cell nucleating agent is titanium dioxide; (c) the cell regulator is ACR-401; (d) the inorganic filler is calcium carbonate; (e) the mass ratio of plasticizer to polyvinyl chloride resin is (55-65):100; (f) the mass ratio of the cell nucleating agent to the polyvinyl chloride resin is (1-3): 1000; (g) the mass ratio of the cell regulator to the polyvinyl chloride resin is (11-13): 100; (h) The mass ratio of inorganic filler to polyvinyl chloride resin is (0.5-1.5):
100.
6. The PVC foam material according to claim 5, characterized in that: The raw materials for preparation meet one or more of the following conditions: (a) The mass ratio of plasticizer to polyvinyl chloride resin is 60:100; (b) The mass ratio of the cell nucleating agent to the polyvinyl chloride resin is 2:100; (c) The mass ratio of the cell regulator to the polyvinyl chloride resin is 12:100; (d) The mass ratio of the inorganic filler to the polyvinyl chloride resin is 1:
100.
7. The method for preparing the PVC foam material according to any one of claims 1 to 6, characterized in that: include: The prepared raw materials are mixed, kneaded and foamed to obtain a PVC foam material.
8. The preparation method according to claim 7, characterized in that: The preparation method meets one or more combinations of the following conditions: (a) firstly mixing a polyvinyl chloride resin, a stabilizer, a plasticizer, a cell nucleating agent, a cell regulator and an inorganic filler to obtain a first mixture; pre-plasticizing the first mixture and stirring it to obtain a second mixture; wherein the pre-plasticizing and stirring are repeated for more than one time; mixing the second mixture with a modifier and a foaming agent, kneading them and foaming them to obtain a PVC foam material; (b) the mixing temperature is 100°C-120°C; (c) Foaming is performed using a mold, and the hot pressing temperature is 160°C-180°C; (d) Foaming is performed using a mold, and the hot pressing time is 8min-10min; (e) Foaming: Use mold foaming, and the cold pressing time is 4min-7min.
9. A shoe sole, characterized in that: The method is prepared from the PVC foam material according to any one of claims 1 to 6.
10. Shoes, characterized in that The invention comprises the sole as claimed in claim 9.
Citation Information
Cited By
Preparation method and system for PVC plate production
CN121133169A